2019
DOI: 10.3390/rs11050588
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Best Hyperspectral Indices in Estimating Plant Species Richness in Sandy Grasslands

Abstract: Numerous spectral indices have been developed to assess plant diversity. However, since they are developed in different areas and vegetation type, it is difficult to make a comprehensive comparison among these indices. The primary objective of this study was to explore the optimum spectral indices that can predict plant species richness across different communities in sandy grassland. We use 7339 spectral indices (7217 we developed and 122 that were extracted from literature) to predict plant richness using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 74 publications
(125 reference statements)
1
13
0
Order By: Relevance
“…Different plant species respond in their own way to incoming solar radiation according to their pigment, water, and biochemical content, as well as leaf and canopy structure. Thus, the variability in the remotely sensed spectra might enable detection of plant species diversity [13][14][15][16][17]. This concept represents the basis of the spectral variability hypothesis (SVH): as the number of plant species increases for a given area, the spectral diversity observed from that area should also increase [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different plant species respond in their own way to incoming solar radiation according to their pigment, water, and biochemical content, as well as leaf and canopy structure. Thus, the variability in the remotely sensed spectra might enable detection of plant species diversity [13][14][15][16][17]. This concept represents the basis of the spectral variability hypothesis (SVH): as the number of plant species increases for a given area, the spectral diversity observed from that area should also increase [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the results achieved in previous studies with respect to herbaceous canopies and grassland types is summarized in Table 1. These studies reported a positive correlation (up to R 2 = 0.58) between spectral diversity metrics and α-diversity in grassland ecosystems [13,14,24]. Aneece et al [24] related spectral diversity (expressed as SD) with species diversity (Shannon-Weiner index) and evaluated correlations (R 2 = 0.43) across different spectral regions from visible (VIS) and near-infrared (NIR).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the use of hyperspectral remote sensing (HRS) data has become common for identifying the composition and physiognomy of forests across large areas [4][5][6][7]. The high spectral resolution of HRS (50-100 nm band width) allows identification of each classified land-cover cluster according to its known spectral signature, thereby enabling detailed analyses of land covers such as mineral composition [8], soil type [9], and vegetation structure and composition [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%